Utilization of carbide lime waste as base catalyst for biodiesel production - Subramaniam K.; Munusamy S.; Pua F.-L.; Nasir M.A.M.; Othman R.; Jaafar S.N.S. (Science Publishing Corporation Inc, 2023)
Calcium rich solid base catalyst was synthesized from local waste carbide lime and its catalytic performance was evaluated visa biodiesel production. Carbide lime waste was used to produce CLW-I and CLW-II solid base catalyst using different preparation methods. Characterization including base strength analysis, scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) were investigated. Catalytic strength was examined by deploying the solid base catalysts for transesterification reaction of palm oil. Fourier Transform Infrared (FTIR) was used to analyze the presence of ester group in biodiesel. The yield of biodiesel conversion was calculated based on the mass of biodiesel and glycerol. The highest biodiesel conversion rate of 75.30% was achieved by CLW-I solid base catalyst at 9% loading. The good catalytic performance of carbide lime waste derived solid base catalysts proves that it has high potential to replace the usage of conventional catalyst in the biodiesel industry. 2018 Authors.